Design Criterion For Zczvt Single-phase Inverters With Magnetically-coupled Auxiliary Pole - Lúcio da Silva Martins, Mário; Marcelo de Oliveira Stein, Carlos; Renes Pinheiro, José; Leães Hey, Hélio (Eletrônica de Potência, 2010)
This paper presents in detail a design methodology for Zero-Current Zero-Voltage Transition inverters with magnetically-coupled auxiliary circuit. These ZCZVT inverters accomplish favorable softswitching conditions with a magnetically coupled auxiliary voltage which is derived directly from the inverter filter inductor. It ensures no resonant auxiliary circuit, reducing circulating reactive energy. The design methodology takes into account the semiconductor requirements to ensure low switching losses on the assisted IGBT modules, which is very important to ensure the best characteristics of the ZCZVT technique. The theoretical analysis is verified experimentally by means of a 1kW, 40 kHz laboratory prototype. The results prove the high efficiency of the prototype implemented according to the proposed design.